Design and Simulation of Microstrip Patch Antenna for Wireless Applications - Ahmed, Kawan F.; Abdullah, Rawaz H. (Kurdistan Journal of Applied Research, 2017)
In this paper two rectangular microstrip patch antennas are designed to operate in and bands, using Computer Simulation Technology (CST) Microwave Studio. The designed antenna can be used for industrial, scientific and medical (ISM) band applications. The RO4350B hydrocarbon ceramic laminates from ROGRES corporation substrate is chosen in the design of the dielectric substrate of the antennas. The designed antenna has low profile, low cost, easy fabrication and good isolation. The parameters such as return loss, voltage standing wave ratio (VSWR), antenna gain, radiation pattern has been simulated and analyzed.